Effect of road traffic on heavy metal concentrations of plants - Yläranta, Toivo (Agricultural and Food Science, 1995)
The concentrations of zinc, copper, lead, cadmium and nickel in spring wheat grain and straw, Italian rye grass and lettuce were studied in a two-year field experiment conducted alongside two roads with a daily traffic density of 9500 and 5500 vehicles each. The experimental plots were located 22, 58 and 200 m from the roads. As controls, polyethylene pots filled with non-contaminated soil were placed in each plot. The values for the bulk deposition of lead were 50% and those for dry deposition over 50% higher in the plot 22 m from the roadside than in the plot 200 m from the roadside. The bulk deposition of zinc also decreased slightly with distance from the road. Cadmium depositions were low at all experimental sites. The highest values for dry deposition of lead and cadmium were recorded when the wind blew from the road in the direction of the collectors. The heavy metal concentrations varied from plant to plant but for a particular species were similar at different experimental sites. The highest zinc, cadmium and nickel concentrations were measured in lettuce. The lead concentration of wheat straw, Italian rye grass and lettuce at 22 m from the roadside was 1.5-3 times that of the background level at 200 m. In wheat grain, the lead concentration was very low and did not change with distance from the road. The plants took up lead mainly from air deposition. The zinc concentration of wheat grain and the nickel concentration of Italian rye grass were also high. Cadmium concentrations were low in wheat grain and straw and in rye grass. In wheat, the zinc and copper concentrations were higher and the lead and cadmium concentrations much lower in grain than in straw.